A development of web-based bernese automated global positioning system processing package - Suryamen Suhasril, Haris (2008)
The Bernese Processing Engine (BPE) in the form of the scripts can be designed to run Bernese programs in an automated mode, and at the same time it can be made accessible online through the internet. By using the internet, more than one computer can run Bernese programs and in turn the program can be executed simultaneously by the same computer. Therefore a single script is needed to control all over the Bernese program, the automated mode of program, interfacing on the web server, the link with the internet, and interaction with the online users at the same time, especially on the user-friendly Windows Operating System. The research methodology which is used is the designing and development of the Automation Script on the website in a personal application server. The server is built by transforming a personal computer using Internet Information Service (IIS). The website for server is developed and simulated by using hypertext technologies of Common Gateway Interface (CGI) and Hyper Text Markup Language (HTML), and interface between server and users is built to link processing area of Bernese software and internet access. The automatic process of Bernese uses the raw data of Global Positioning System (GPS) and the result is compared with manual processing. Through this research Bernese processing software version 4.2 shows that the program can be modified to run in automatic process and on the web server. The knowledge of development of the Web-based Global Positioning System (GPS) automated mode will be made accessible for contribution and dissemination of the automated solutions of the GPS data from International GPS Service (IGS) stations and helping other projects to produce straightforward results, particularly for the Universiti Teknologi Malaysia (UTM).